Frequency of blaOxa10 Beta-lactamase gene in Pseudomonas aeruginosa isolated from different clinical swabs - AL- Rubaye, Dalal; Albassam, Wasan; al-habobi, Hayder; AL-Rubaye, Ilham (Iraqi Journal of Science, 2025)
Thirty one isolates of P. aeruginosa were collected from 100 clinical samples include (pus, burn and wound swabs). All the isolates were identified as P. aeruginosa by conventional methods, PCR and DNA sequencing. Antibiotic sensitivity tests were undertaken for 8 groups of antibiotics (Cephalosporins, Rifamycin, fluoroquinolones, Penicillins, Carbapenems, Aminoglycosides, Chloramphenicol and Beta-lactamase inhibitor+ Penicillin). The highest resistance rate was recorded to Rifampin, and Pipracillin with 31(100%), followed by Chloramphenicol ,Cefotaxime and Cefixime with 28 (90.3%), and the lowest resistance rate to Imipenem with 8 (25.8%). Cefpodoxime resistance value was less than values reported in other study. Six strains did not carry the blaOXA10 gene that is hydrolyze Cloxacillin , Oxacillin and Carbapenem, in spite of their resistance to more than 3 different antibiotic group. According to present study, we concluded that the drug of choice is the Imipenem, the most effective anti-pseudomonal agent, and the bla OXA-10 gene frequency was 6 (19.4%) among P. aeruginosa isolates from patients in different hospitals in Baghdad.